Transient loss of consciousness without cerebral origin following injection of Sinopharm vaccine - Bakhtiar Ebrahimirad; Hero Payandeh (Journal of Preventive and Complementary Medicine)
Background: The Sinopharm vaccine has been widely administered in Iran during COVID-19 pandemic. Clinical trials have identified several side effects associated with the Sinopharm vaccine, including pain at the injection site, fatigue, headache, and lethargy. It is essential for individuals to be informed about these potential side effects.Case Presentation: The patient was a 32-year-old woman who presented to the hospital emergency room following her second dose of the COVID-19 vaccine. Initial assessments revealed that all hemodynamic parameters were normal, her respiratory pattern and rhythm were stable, and her SpO2 was above 94%. The GCS was utilized to evaluate her level of consciousness, which was assessed at 3 out of 15. Cardiac and respiratory monitoring was initiated, along with oxygen therapy via face mask. Comprehensive evaluations, including blood tests, ECG, echocardiogram, chest CT scan, and brain MRI/MRV, were performed, all of which returned normal results. The patient regained full consciousness two days after admission to the ICU and was discharged in good general condition after four days in the hospital.Conclusion: Individuals vaccinated against COVID-19 may experience reactions following the injection. These reactions are expected and indicate that the immune system is effectively responding to the vaccine. The side effects associated with the Sinopharm vaccine vary in severity. Given that this patient had no prior medical history and all diagnostic tests were normal, her transient loss of consciousness may be attributed to the rare side effects of the Sinopharm vaccine.